2011
DOI: 10.1038/leu.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

The serine/threonine kinase Pim-2 is a novel anti-apoptotic mediator in myeloma cells

Abstract: Bone marrow stromal cells (BMSCs) and osteoclasts (OCs) confer multiple myeloma (MM) cell survival through elaborating factors. We demonstrate herein that IL-6 and TNF family cytokines, TNFa, BAFF and APRIL, but not IGF-1 cooperatively enhance the expression of the serine/threonine kinase Pim-2 in MM cells. BMSCs and OCs upregulate Pim-2 expression in MM cells largely via the IL-6/STAT3 and NF-jB pathway, respectively. Pim-2 short interfering RNA reduces MM cell viability in cocultures with BMSCs or OCs. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
122
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(132 citation statements)
references
References 20 publications
7
122
0
3
Order By: Relevance
“…Furthermore, and consistent with an additive rather than epistatic effect on TSC2, the previous work by Asano et al 6 reported that treatment with the Pim2 inhibitor and LY294002 (PI3K inhibitor) cooperatively suppressed MM cells viability.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Furthermore, and consistent with an additive rather than epistatic effect on TSC2, the previous work by Asano et al 6 reported that treatment with the Pim2 inhibitor and LY294002 (PI3K inhibitor) cooperatively suppressed MM cells viability.…”
supporting
confidence: 50%
“…6,7 By counteracting the methylated status of H3K4, Jarid1b would shift the balance toward repression of these genes, and conversely its knockdown would favor gene activation (see figure). This is obviously a highly simplistic model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Pim kinases, particularly Pim-2, are known to be downstream of B-lymphocyte stimulator and NF-B, and are both regulator and target of STAT3. [48][49][50] All of these pathways interconnect, and it is reasonable to postulate potential overlap and interactions between Pim kinases and these growth or transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In AML, this is driven at least in part by activation of receptor tyrosine kinases such as the Flt3-internal tandem duplication (Flt3-ITD) mutation 5,7,8 found in approximately one third of AML patients. The JAK/STAT pathway, a key mediator of cytokine and growth factor signaling, plays an important role in regulating Pim expression.…”
Section: Introductionmentioning
confidence: 99%